Increased Cystatin C in Astrocytes of Transgenic Mice Expressing the K670N-M671L Mutation of the Amyloid Precursor Protein and Deposition in Brain Amyloid Plaques - Tiana Steinhoff; Eva Moritz; M.Axel Wollmer; M.Hasan Mohajeri; Stefan Kins; Roger M. Nitsch (Neurobiology of Disease, 2001)
Cystatin C is an essential secretory cofactor for neurogenesis with potent protease inhibitor activities. Polymorphisms of cystatin C are genetically associated with Alzheimer's disease (AD), and the L68Q mutation causes hereditary cerebral hemorrhage with amyloidosis of the Icelandic type, in which cystatin C and β-amyloid are colocalized in cortical blood vessels. To determine whether cystatin C and β-amyloid also colocalize in brain amyloid plaques, we analyzed transgenic mice expressing the Swedish APP (SweAPP) mutation. We found high levels of cystatin C in astrocytes surrounding β-amyloid plaques, and discrete layers of cystatin C attached to amyloid plaque cores covered by a layer of β-amyloid. In addition, cystatin C accumulated in reactive astrocytes throughout the brain, independently of, and before the onset of, amyloid plaque formation. These results show that expression of SweAPP is associated with increased cystatin C in reactive astrocytes, and they suggest an early role of cystatin C in appositional amyloid plaque growth.